Current State of Preeclampsia Mouse Models: Approaches, Relevance, and Standardization - Waker, Christopher A.; Kaufman, Melissa R.; Brown, Thomas L. (Frontiers in Physiology, 2021)
Preeclampsia is a multisystemic, pregnancy-specific disorder and the leading cause of maternal and fetal death. Preeclampsia is also associated with an increased risk for chronic morbidities later in life for mother and offspring. Abnormal placentation or placental function has been well-established as central to the genesis of preeclampsia; yet much remains to be determined about the factors involved in the development of this condition. Despite decades of investigation and many clinical trials, the only definitive treatment is parturition. The impediment to improved treatment may be a result of the many different animal models used to study preeclampsia and the wide variety of physiological endpoints that are evaluated. Many approaches to simulate preeclampsia in mice have been developed and include mixed mouse strain crosses, genetic overexpression and knockout, exogenous agent administration, surgical manipulation, systemic adenoviral infection, and trophoblast-specific gene transfer. These models have been useful to investigate how biological perturbations identified in human preeclampsia are involved in the generation of preeclampsia-like symptoms and have improved the understanding of the molecular mechanisms underpinning the human condition. However, many of these approaches have aspects that lack physiological relevance to this human disorder and may interfere with therapy development and testing. This report provides a comprehensive review of mouse models that exhibit preeclampsia-like symptoms and a proposed standardization of physiological characteristics for analysis in murine models of preeclampsia.